A Study on Tourist Push and Pull Motives to Visit Farm Tourism Sites in Kerala - Neethu, M. C; Ramyaprabha, N (Indian Journal of Information Sources and Services, 2025)
Farm tourism has grown in popularity in Kerala, India, attracting a diverse range of tourists looking for authentic and immersive agricultural experiences. This research investigates the push and pull factors influencing farm tourists in Kerala. A convenience sampling technique was used to collect the sample of 200 tourists randomly selected from various parts of Kerala. Statistical tools such as simple percentages, chi-square test, factor analysis, and weighted average method were used to analyze the collected data. Understanding these factors allows tourism stakeholders and local communities to better tailor their offerings to meet the needs and desires of farm tourists, maximizing the potential benefits of this growing niche market.